2017
DOI: 10.4309/jgi.2017.35.5
|View full text |Cite
|
Sign up to set email alerts
|

Quelle est l’influence du genre dans la recherche de soins chez les joueurs?

Abstract: Cette étude vise à décrire l’influence du genre sur les différentes étapes amenant un joueur ayant des problèmes de jeu à prendre la décision de rechercher de l’aide. Le modèle de recherche d’aide de Goldsmith, Jackson et Hough (1988) a été utilisé pour conceptualiser les étapes de prise de décision menant à consulter des services d’aide pour un problème de jeu de hasard et d’argent. Au total, 83 participants, dont 45 femmes et 38 hommes adultes, y ont pris part. Les résultats indiquent que, comparativement au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
0
1
Order By: Relevance
“…Moreover, our findings diverge from other determinations from samples of women gamblers recruited in treatment centres. In fact, several studies have reported that women with gambling problems are at higher risk of also having mental health problems such as depression (e.g., Beaulac et al, 2017). The present study does not support the finding that depression and anxiety can be good predictors of gambling problems in women poker players.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, our findings diverge from other determinations from samples of women gamblers recruited in treatment centres. In fact, several studies have reported that women with gambling problems are at higher risk of also having mental health problems such as depression (e.g., Beaulac et al, 2017). The present study does not support the finding that depression and anxiety can be good predictors of gambling problems in women poker players.…”
Section: Discussioncontrasting
confidence: 99%